Psikoedukasi Dalam Upaya Pencegahan Fear of Missing Out (FoMO) Pada Siswa SMA X - Alexander, Alfyola DwiYuan; Ridfah, Ahmad (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
As a generation that grew up in a time of internet and digital advances, the millennial generation (Gen Z) is a generation that is always connected to one another. With this increasingly sophisticated technology, the level of internet usage is increasing, especially the use of social media. This can also trigger increased anxiety felt by its users, such as they will feel anxiety which leads to fear of being left behind from information about other people on social media. This phenomenon is known as FoMO (Fear of Missing Out). In connection with the problems obtained, the researchers provided psychoeducation which was carried out indirectly or online. This psychoeducation is carried out by distributing posters that have been made using the Canva editor application on social media, namely Instagram social media. The target of this psychoeducation is everyone who uses Instagram social media, especially students of SMA Kartika XX-1 Makassar. By holding this psychoeducation, it is hoped that it can increase the understanding of SMA Kartika XX-1 Makassar students regarding the impact and ways of dealing with the FoMO phenomenon. Based on the results of the psychoeducation that has been given, it was found that there was an increase in students’ understanding of the FoMO phenomenon as indicated by the feedback in the form of comments, likes, and responses given to poster posts that had been posted on Instagram social media accounts.